Hungary and Dutch Fencing Diplomacy after the First World War: (Халықаралық қатынастар және халықаралық құқық сериясы, 2024)
In the restoration of Hungarian sovereignty after the First World War, the Hungarian officers of the Austro-Hungarian Army (K. und k. Leger) played an important role. They were generally trained at the Austro-Hungarian Military Academy, the Theresianum in Wiener-Neustadt, Austria, where they were required to participate in a course to become a teacher of military fencing and gymnastics. These military fencers made a significant contribution to the reconstruction of Hungarian state institutions after the First World War. This article argues that a delegation of Dutch military fencers led by one of the most prominent fencers of his time Adriaan Egbertus Willem 'Arie' de Jong (1882-1966) established close contact with the Hungarian fencing elite and that these fencing contacts were part of a broader Dutch diplomatic offensive to re-involve the coalition of the Central Powers and their successor states in European political relations. The fencing activities of Arie de Jong and his team and in the background the sports diplomatic activities of Olympic fencer and sports director George van Rossem (1882-1955) were of decisive importance in regaining Hungary a position in international sports organizations in post-war Europe.Keywords: Hungary, fencing, Treaty of Trianon, László Borsody, Arie de Jong, George van Rossem, fencing diplomacy